Peran Relasi Timbal Balik di Era Globalisasi dalam Petuah Jawa dan Lamaholot - Dwika Tegar Ardiansah; Yufensia Afriantis Gowo Making; Anselmus Wikan Wicaksono (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2026)
The era of globalization demands innovation and emphasizes the importance of reciprocal relationships between humans and nature, as well as between humans themselves. Nature provides for human needs, while humans must contribute in return. However, exploitation of nature without reciprocity often occurs. In human relationships, especially between the old and the young, there has been a shift in roles; in the past, the young learned from the old, but now the old must also learn from the young. This study uses literature review and interviews to explore the ethical imperative of the advice “Kebo Nyusu Gudel” from Java and “Lewotana molo nage kame dore, Teti pana ake todok, Gawe ake wale” from Lamaholot. The three main questions are: What is the literal meaning of this advice? How do these sayings function as instruments in Javanese and Lamaholot society? What is the relevance of these sayings to relational roles in the era of globalization? The results of the study show the importance of human awareness in appreciating reciprocal relationships, the ethical message to continue learning and appreciating, and the relevance of these sayings as an answer to the importance of reciprocal relationships in the lives of Javanese and Lamaholot communities in the era of globalization.AbstrakEra globalisasi menuntut inovasi dan menegaskan pentingnya relasi timbal balik antara manusia dan alam serta antar manusia. Alam memberi kebutuhan kepada manusia, sementara manusia harus memberi kontribusi kembali. Meski sering terjadi eksploitasi alam tanpa timbal balik. Dalam hubungan antar manusia, khususnya antara yang tua dan muda, terjadi perubahan peran; dulu yang muda belajar dari yang tua, kini yang tua juga harus belajar dari yang muda. Penelitian ini menggunakan studi pustaka dan wawancara untuk mengeksplorasi imperatif etis petuah “Kebo Nyusu Gudel” dari Jawa dan “Lewotana molo nage kame dore, Teti pana ake todok, Gawe ake wale” dari Lamaholot. Tiga pertanyaan utama adalah: Apa makna literal petuah ini? Bagaimana petuah menjadi instrumen dalam masyarakat Jawa dan Lamaholot? Apa relevansi petuah terhadap peran relasi di era globalisasi? Hasil penelitian menunjukkan pentingnya kesadaran manusia menghargai relasi timbal balik, pesan etis untuk terus belajar dan menghargai, serta relevansi petuah sebagai jawaban atas pentingnya keterhubungan relasi timbal balik dalam kehidupan masyarakat Jawa dan Lamaholot di era global.